Experimental investigation of cold adhesion failure physical mechanism of gold plated contact within the Micro-Electromechanical-Relay. (March 2021) - Ren, Wanbin; Zhang, Chao; Du, Qingfeng; Du, Danyang; Wang, Hai
Highlights: The cold adhesion force of gold plated contacts resulted by the fretting is observed. Surface quality of gold coating and static contact force are the key factors influencing the adhesion phenomena. The cold adhesion failure physical model is built with the help of mechanical adhesion theory. Effect of fretting amplitude and fretting cycle on the adhesion force is investigated explicitly. The nature of cold adhesion resulted by fretting behavior is the mechanical locks within the contact asperities. Abstract: Gold plated contacts are widely used in the Micro-Electromechanical-Relay to improve electric contact reliability. However, the cold adhesion phenomenon between gold plated surfaces is prone to cause normally closed contacts operating failure. In this paper, a novel test rig for measuring dynamic force and contact resistance between spring contact and rod shape contact during breaking process is introduced. The dynamic contact force, displacement and contact resistance during contact breaking process are obtained. From these waveforms, the adhesion force between two contacts in each break is estimated. In order to reveal the failure phenomena occurred in the mechanical vibration screening tests, fretting between the closed contact pairs is generated with different amplitudes and cycles by using the motorized stage. Subsequently, the effects of fretting behaviors on cold adhesion of gold plated contact pairs are investigated explicitly. Next, the associated failure physical model is built with the help of mechanical adhesion theory to explain the nature of surface adhesion. Furthermore, surface quality of gold coating and static contact force are also verified as the key factors influencing the adhesion phenomena. Surface morphologies of contacts prove the substantial increase of adhesion force correlates closely with the features of micro asperities.